[AG180-reviewed] Silage Harvesting, Storing, and Feeding - Adegbola T. Adesogan; Yoana C. Newman (EDIS, 2010)
Revised! SS-AGR-177, an 8-page illustrated fact sheet by A. T. Adesogan and Y. C. Newman, discusses the advantages, disadvantages, and phases of silage fermentation and the factors affecting silage quality. Published by the UF Department of Agronomy, September 2010.